Design of kinematic connectors for microstructured materials produced by additive manufacturing - Silva, Miguel R. (2021)
The main characteristic of materials with a functional gradient is the progressive composition or the structure variation across its geometry. This results in the properties variation in one or more specific directions, according to the functional application requirements. Cellular structure flexibility in tailoring properties is employed frequently to design functionally-graded materials. Topology optimisation methods are powerful tools to functionally graded materials design with cellular structure geometry, although continuity between adjacent unit-cells in gradient directions remains a restriction. It is mandatory to attain a manufacturable part to guarantee the connectedness between adjoining microstructures, namely by ensuring that the solid regions on the microstructure’s borders i.e., kinematic connectors) match the neighboring cells that share the same boundary. This study assesses the kinematic connectors generated by imposing local density restrictions in the initial design domain (i.e., nucleation) between topologically optimised representative unit-cells. Several kinematic connector examples are presented for two representatives unit-cells topology optimised for maximum bulk and shear moduli with different volume fractions restrictions and graduated Young’s modulus. Experimental mechanical tests (compression) were performed, and comparison studies were carried out between experimental and numerical Young’s modulus. The results for the single maximum bulk for the mean values for experimental compressive Young’s modulus (<semantics>E<mover accent="true">x¯</mover></semantics>) with 60<semantics>%<mspace width="3.33333pt"></mspace>Vf</semantics> show a deviation of <semantics>9.15%</semantics>. The single maximum shear for the experimental compressive Young’s modulus mean values (<semantics>E<mover accent="true">x¯</mover></semantics>) with 60<semantics>%<mspace width="3.33333pt"></mspace>Vf</semantics>, exhibit a deviation of <semantics>11.73%</semantics>. For graded structures, the experimental mean values of compressive Young’s moduli (<semantics>E<mover accent="true">x¯</mover></semantics>), compared with predicted total Young’s moduli (<semantics>ESe</semantics>), show a deviation of <semantics>6.96</semantics> for the bulk graded structure. The main results show that the single type representative unit-cell experimental Young’s modulus with higher volume fraction presents a minor deviation compared with homogenized data. Both (i.e., bulk and shear moduli) graded microstructures show continuity between adjacent cells. The proposed method proved to be suitable for generating kinematic connections for the design of shear and bulk graduated microstructured materials.